THE CORRELATION BETWEEN DENTAL CARIES AND ORAL HEALTH RELATED QUALITY OF LIFE AMONG VISUALLY IMPAIRED CHILDREN - Oktadewi, Fitri Diah; Soeprihati, Indah Titien; Hanindriyo, Lisdrianto (Odonto : Dental Journal, 2020)
Background: Visually impaired children have a low vision to visualize the process of plaque removal on teeth resulting in dental caries progression. Dental caries has an impact on childrenâ€™s quality of life. The impact of dental caries on oral health related quality of life among visually impaired children remains mostly unknown. This study aimed to determine the correlation between dental caries and oral health related quality of life (OHRQoL) among visually impaired children.Method: This study was an observational study with a cross sectional design and conducted across four regencies in Yogyakarta and Central Java Province. A total of 70 visually impaired children aged 7-18 participated in this study. The participants underwent a dental examination to determine their caries experience using DMFT/dmft index. Oral health related quality of life was measured using the COHIP SF 19 questionnaire with interviewing method.Result: Data analysis showed that caries frequency was 94,3%. The mean number of DMFT/dmft index was 4,8 Â± 2,743. Spearman correlation test showed the p value was 0,611 (p>0,05) for the correlation between DMFT/dmft index and OHRQoL.Conclusion: This study showed no correlation between dental caries and oral health related quality of life among visually impaired children.